Indications and outcome after lung transplantation in children under 12 years of age: a 16-year single center experience - Iablonskii, Pavel; Carlens, Julia; Mueller, Carsten; Aburahma, Khalil; Niehaus, Adelheid; Boethig, Dietmar; Franz, Maximilian; Floethmann, Katharina; Sommer, Wiebke; Optenhoefel, Joerg; Tudorache, Igor; Greer, Mark; et al. (The journal of heart and lung transplantation, 2022)
Objective - : Paediatric lung transplantation poses unique management challenges. Experience regarding indications and outcome is scarce, especially in younger children. The primary aim of this study was to investigate outcome after first lung transplantation in children <12 years of age in comparison to adolescents (12-17 years old). - Methods - : Records of patients <18 years who underwent first lung transplantation between 01/2005 and 01/2021 were retrospectively reviewed, and compared between children <12 years old and adolescents. Median (IQR) follow-up was 51 (23-91) months. - Results - Of the 117 patients underwent first lung transplantation at our institution, of whom 42 (35.8%) patients were <12 years and 75 (64.2%) ≥12 years old. Compared to adolescents, children were more often transplanted for interstitial lung disease (33.3% vs 12%, p = 0.005) and precapillary pulmonary hypertension (28.6% vs 12%, p = 0.025), and required more often intraoperative cardiopulmonary bypass (31% vs 14.7%, p = 0.036) and postoperative ECMO support (47.6% vs 13.3%, p < 0.001). Postoperatively, children required longer ventilation times (78 vs 18 hours, p = 0.009) and longer ICU stay (9.5 vs 3 days, p < 0.001) compared to their older counterparts. Primary graft dysfunction grade 3 at 72 hours (9.5% vs 9.3%, p = 0.999), in-hospital mortality (2.4% vs 6.7%, p = 0.418), graft survival (80% vs 62%, p = 0.479) and freedom from chronic lung allograft dysfunction (76% vs 59%, p = 0.41) at 8-year follow-up did not differ between groups. - Conclusions - : Lung transplantation in children under 12 years is challenging due to underlying medical conditions and operative complexity. Nevertheless, outcomes are comparable to those in older children.